Image Extraction in OpenCV Using the Local Binary Pattern Method - Hapsari, Nani Sarah; Fatman, Yenni; Sugiarto, Bambang (Journal of Software Engineering, Information and Communication Technology (SEICT), 2024)
This research aims to implement the Local Binary Pattern (LBP) method for image extraction in OpenCV software. This method separates the objects' characteristics in the image to be recognized accurately. The research process involves stages of device configuration, image data preprocessing, and implementation and evaluation of extraction results. The research results show that the LBP method produces images with various patterns, such as grayscale, the original LBP shape, and other variations. This study also discusses the application of edge detection, histogram, thresholding, and equalization for image processing. Implementation of this method opens up opportunities for further development in various areas, including object identification, video, and wood imagery.